A Review of Accounting Skills Acquisition in Business Education, Enhancing Career Success - Sani, Amina; Muhammad, Kibuuka; Aliyu, Zainab Garba (NIU Journal of Humanities, 2018)
Accounting skill was found to be contributory to entrepreneurial performance and as such entrepreneurs are advised to embark on capacity building in accounting skill in the area of financial management and record keeping. Entrepreneurs are agents and drivers of development in most economies of the world including Nigeria. Accounting is the core academic discipline that aids the entrepreneurial drive given the popular opinion that is the language of business. The objective of this study is to examine the role of accounting on entrepreneurship education for self- reliance and sustainable development in Nigeria. The study considered the accounting profession and the major role it plays in entrepreneurship development. It is the submission of the authors that entrepreneurs with basic accounting knowledge and entrepreneurial skills stand better chances of becoming self- reliant and attaining business success. The paper recommends among other things that government should remove those obstacles that militate against entrepreneurial development in Nigeria.